Total synthesis of (S)-(-)-curvularin: a ring-closing-metathesis-based construction of the macrocyclic framework - Mohapatra, Debendra K.; Rahaman, Hasibur; Pal, Rita; Gurjar, Mukund K. (Synlett, 2008)
A convergent, flexible, and efficient approach to the synthesis of curvularin is described. Key step is the high-yielding macrocyclic ring formation by ring-closing metathesis (RCM) using the Grubbs second-generation catalyst.
Keywords: curvularin; Cytotoxic; Pinnick oxidation; Ring-closing metathesis; Wittig reaction

Total syntheses and absolute stereochemistry of decarestrictines C-1 and C-2 - Mohapatra, Debendra K.; Sahoo, Gokarneswar; Ramesh, Dhondi K.; Rao, J. Srinivasa; Sastry, G. Narahari (Tetrahedron Letters, 2009)
The total syntheses of decarestrictines C-1 and C-2 have been described. The synthetic strategy involves a practical and flexible approach using esterification and ring-closing metathesis to unite the acid and alcohol fragments. The acid fragments are enantiomers of each other and have been prepared from L-(-)-malic acid via similar transformations; in Sharpless asymmetric epoxidation, (+)-DET has been used for decarestrictine C-1 and (-)-DET for decarestrictine C-2. The alcohol fragment is identical for both decarestrictines C-1 and C-2 and has been accessed from D-(+)-mannitol. Comparison of the H-1 and C-13 NMR data combined with the computational studies predicts the presence of two conformations without and with hydrogen bonding (conformational isomers I and II for decarestrictine C-1), respectively. The H-1 and C-13 NMR data for decarestrictine C-2 completely agreed with the analytical data reported by Kibayashi et al. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decarestrictines; Pinnick oxidation; Ring-closing metathesis; Sharpless asymmetric epoxidation; Yamaguchi coupling reaction

Carbohydrate based total synthesis of xestodecalactone B and C: revision of the absolute configuration - Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Current Organic Chemistry, 2012)
A convergent chiral pool approach for the total synthesis of xestodecalactones B and C was demonstrated in which intramolecular acylation reaction constituted the key step. Synthetic and spectroscopic studies reported herein, suggested that the previously assigned structures of xestodecalactone B and C be interchanged.
Keywords: Chiral pool; Hydroboration; Intramolecular acylation; Pinnick oxidation; Revision of absolute configuration; Xestodecalactone B and C